SISTEM INFORMASI AKUNTANSI ANALISA LAPORAN KEUANGAN PADA PUSAT KOPERASI PEGAWAI REPUBLIK INDONESIA KENDAL MENGGUNAKAN METODE RASIO - Edy Siswanto; Laksamana Rajendra Haidar Azani Fahmi; Moh. Muthohir; Sukemi Kamto Sudibyo; Sonia Varian Valmai (LPPM Politeknik Pratama, 2022)
The Republic of Indonesia Employee Cooperative Center in Kendal Regency is a civil servant cooperative center in Kendal Regency which provides savings and loan services for its members.So far, the Indonesian Civil Servant Cooperative, Kendal Regency, does not yet have a special information system in managing finances, making financial reports and financial analysis activities. This causes the performance of cooperative employees to be slow, difficulties in finding customer data, loss of transaction data and presentation of information and analysis of cooperative financial statements takes a long time.With the implementation of an accounting information system for analyzing financial statements at the Indonesian Employee Cooperative, Kendal Regency using the financial ratio analysis method, it will be able to assist in managing finances in a database that is able to produce financial reports and analyze th